Contingency Management of Health Care Organizations: It Depends. Issue 1 (January 2016) - Olden, Peter C.
Abstract : Managers in health care organizations (HCOs) must perform many processes and activities, such as planning goals, designing organization structure, leading people, motivating employees, making decisions, and resolving conflict. How they do all this strongly affects the performance and outcomes of their organizations and themselves. Some managers develop a usual way of performing their jobs and achieve some success with a preferred method of leading or a favorite approach to motivating. However, their success will be limited if they always rely on a standard "1-size-fits-all" approach. This is because contingency factors influence the effectiveness of a given approach to managing. The "best" approach depends on contingency factors, including the situation and the people involved. Managers should choose an approach to fit with the changing contingency factors. This article explains why and how managers should develop a contingency approach to managing HCOs. The development of contingency theory is briefly described. Practical application of contingency management is explained for leading, motivating, decision making, and resolving conflict. By using a contingency approach, managers can be more effective when managing their HCOs.